Mexican women in American factories : free trade and exploitation on the border - Tuttle, Carolyn (University of Texas Press, 2012)
Prior to the millennium, economists and policy makers argued that free trade between the United States and Mexico would benefit both Americans and Mexicans. They believed that NAFTA would be a "win-win" proposition that would offer U.S. companies new markets for their products and Mexicans the hope of living in a more developed country with the modern conveniences of wealthier nations. Blending rigorous economic and statistical analysis with concern for the people affected, Mexican Women in American Factories offers the first assessment of whether NAFTA has fulfilled these expectations by examining its socioeconomic impact on workers in a Mexican border town. Carolyn Tuttle led a group that interviewed 620 women maquila workers in Nogales, Sonora, Mexico. The responses from this representative sample refute many of the hopeful predictions made by scholars before NAFTA and reveal instead that little has improved for maquila workers. The women?s stories make it plain that free trade has created more low-paying jobs in sweatshops where workers are exploited. Families of maquila workers live in one- or two-room houses with no running water, no drainage, and no heat. The multinational companies who operate the maquilas consistently break Mexican labor laws by requiring women to work more than nine hours a day, six days a week, without medical benefits, while the minimum wage they pay workers is insufficient to feed their families. These findings will make a crucial contribution to debates over free trade, CAFTA-DR, and the impact of globalization.